GAMBARAN PENGETAHUAN DAN SIKAP SANTRI TENTANG SCABIES DI PONDOK PESANTREN KOTA PEKANBARU - Ramadhan, Padillah; Arneliwati, Arneliwati; Dewi, Ari Pristiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Scabies is an infectious skin disease caused by Sarcoptes scabies hominis variants. Scabies is found in all countries with variety of prevalence. Scabies decreases quality of life and academic achievement, so it needs to be prevented by good knowledge, attitudes and personal hygiene practices on santri. The purpose of the study was to describe the knowledge and attitudes of students about scabies at the Pekanbaru City Islamic Boarding School. This study used quantitative methods with descriptive research design. This research was conducted at Al-Kautsar Islamic Boarding School in Pekanbaru City with 75 santri as sample. The instrument used in this study was a knowledge and attitude questionnaire. The results showed that the majority of respondens aged 12 years old were 70 people (93.3%). The results of the measurement on the level of knowledge are obtained in the category of bad knowledge that is as many as 34 people (45.3%), and the results of measuring the attitudes of santri towards Scabies are found that 42 students (56%) have a positive attitude. The results of this study are expected to be a database for Islamic Boarding School to be the initial data to prevent scabies in order to improve the quality of life and academic achievement of their santri.keywords: Attitude, Knowledge, Scabies